Factors that influence healing of chronic venous leg ulcers: a retrospective cohort - Scotton, Marilia Formentini [UNESP] (2014)
BACKGROUND: Venous ulcers have a significant impact on patient quality of life, and constitute a worldwide public health problem. Treatment is complex, with high failure rates.OBJECTIVES: To identify clinical and therapeutic factors that influence healing of venous ulcers.METHODS: Retrospective cohort study of patients with venous ulcers. Ulcer area was measured at the first visit (T0) and after 6 months (T6) and 1 year (T12). A reduction in ulcer area of 50% or more at T6 and T12 was the outcome of interest, weighted by clinical, demographic and treatment aspects.RESULTS: Ninety-four patients were included (137 ulcers). A reduction in ulcer area of 50% or more was seen in 40.1% of patients (95% CI 31.9 to 48.4%) at T6 and 49.6% (95% CI 41.2 to 58.1%) at T12. Complete healing occurred in 16.8% (95% CI 10.5 to 23.1%) at T6 and 27% (95% CI 19.5 to 39.5%) at T12. The lowest ulcer area reductions at T6 were associated with longstanding ulcer (RR=0.95; 95% CI 0.91 to 0.98), poor adherence to compression therapy (RR=4.04; 95% CI 1.31 to 12.41), and infection episodes (RR=0.42; 95% CI 0.23 to 0.76). At T12, lower reductions were associated with longstanding ulcer (RR=0.95; 95% CI 0.92 to 0.98), longer topical antibiotic use (RR=0.93; 95% CI 0.87 to 0.99), and systemic antibiotic use (RR=0.63; 95% CI 0.40 to 0.99).CONCLUSIONS: Longstanding ulcer, infection, poor adherence to compression therapy, and longer topical and systemic antibiotic use were independently correlated with worse healing rates.